Modelling Optical Waveguide Bends by the Method of Lines - Ary Syahriar; Nabil Rayhan Syahriar; Jusman Syafiie Djamal (Universitas Ahmad Dahlan, 2018)
A rigorous analytical and semi analytical method of lines has been used to calculate the transverse-electric field attenuation coefficient of guided mode as it travels in waveguide bends structure. Both approaches then were compared to get a better understanding on how the attenuation behaves along single curve waveguides with constant radius of curvature. The Helmholtz Equation in polar coordinate was transformed into a curvalinier coordinate to simulate the waveguide bends using the method of line analysis. The simple absorption boundary conditions are used into the method of lines to demonstrate evanescent field of the guided mode nature as its travels in waveguide bends structures. The results show that a reasonable agreement between both theoretical approaches.